PENGARUH MEDIA KARET BAN TERHADAP KETERAMPILAN TIGER SPRONG SENAM LANTAI - Agung Sedayu; Mimi Haetami; Eka Supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this research is, 1) The jump is not curved but rather flat, 2) the jump is too high, 3) too far or too close does not match the strength of the jump, hands are not broken strong, too fast or vice versa too late to bow your head can cause your back or face to fall to the floor, 4) foot repulsion not straight.The purpose of this study was to determine the importance of using various learning media for rubber tires on the results of Tiger Sprong Gymnastics Floor Skills for Students PJKR REG A ILMU KEOLAHRAGAAN FKIP UNTAN. The method used in this study is an experimental method with an experimental design form that is Pre-experimental design. The population in this study were students PJKR 2019 which numbered 61 people. In this study the sample used was 42 students using purposive sampling. Data analysis was performed using t-tes,. the results of data analysis in this study after being treated using rubber tire media in Tiger Sprong Gymnastics Floor Skills for Students PJKR REG A 2019, the results of data analysis obtained by ttest is 13.125> ttable 1.684, with degrees of freedom db = (D-1) is 42-1 = 41 at the 5% significance level with an increase of 33.12%. Based on the results of calculations using t-test analysis, it can be concluded that there is an influence of the tire rubber media on the Tiger Sprong floor gymnastic skills, this is because students are more interested in following the Tiger Sprong floor gymnastics skills after using variations of the tire rubber media in the learning process.Keywords: Gymnastics.  Media, Tiger SprongAbstractThe problem in this research is, 1) The jump is not curved but rather flat, 2) the jump is too high, 3) too far or too close does not match the strength of the jump, hands are not broken strong, too fast or vice versa too late to bow your head can cause your back or face to fall to the floor, 4) foot repulsion not straight.The purpose of this study was to determine the importance of using various learning media for rubber tires on the results of Tiger Sprong Gymnastics Floor Skills for Students PJKR REG A ILMU KEOLAHRAGAAN FKIP UNTAN. The method used in this study is an experimental method with an experimental design form that is Pre-experimental design. The population in this study were students PJKR 2019 which numbered 61 people. In this study the sample used was 42 students using purposive sampling. Data analysis was performed using t-tes,. the results of data analysis in this study after being treated using rubber tire media in Tiger Sprong Gymnastics Floor Skills for Students PJKR REG A 2019, the results of data analysis obtained by ttest is 13.125> ttable 1.684, with degrees of freedom db = (D-1) is 42-1 = 41 at the 5% significance level with an increase of 33.12%. Based on the results of calculations using t-test analysis, it can be concluded that there is an influence of the tire rubber media on the Tiger Sprong floor gymnastic skills, this is because students are more interested in following the Tiger Sprong floor gymnastics skills after using variations of the tire rubber media in the learning process.  Keywords: Gymnastics.  Media, Tiger Sprong